2016
DOI: 10.1039/c5cy02181b
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen pool from YBaCo4O7-based oxides for soot combustion

Abstract: Soot, often referred to as black carbon emitted from diesel engines, is not only a particulate matter pollutant but also a light-absorbing agent that may affect global climate, but can be effectively controlled using a catalytic diesel particulate filter (DPF). A new YBaCo 4 O 7+δ-type oxygen storage material is reported as an effective catalyst for soot combustion. Isotopic isothermal reactions demonstrate the activation of gaseous oxygen and subsequent oxygen storage and reaction/desorption during an oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The peaks with typical structure characteristics of LDHs were clearly observed in all samples. In the case of Co/CoFe−C, the (003), (006), (012), (015), (018), (110), (113) and (1013) basal reflection planes (JCPDS Card NO.50‐0235) were observed at about 11.4°, 23.2°, 34.0°, 38.5°, 46.0°, 58.9°, 60.4° and 64.4°, respectively . The corresponding basal spacing (d003) of Co/CoFe−C, Co/NiFe−C and Co/ZnFe−C were about 0.78 nm, 0.78 nm and 0.68 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks with typical structure characteristics of LDHs were clearly observed in all samples. In the case of Co/CoFe−C, the (003), (006), (012), (015), (018), (110), (113) and (1013) basal reflection planes (JCPDS Card NO.50‐0235) were observed at about 11.4°, 23.2°, 34.0°, 38.5°, 46.0°, 58.9°, 60.4° and 64.4°, respectively . The corresponding basal spacing (d003) of Co/CoFe−C, Co/NiFe−C and Co/ZnFe−C were about 0.78 nm, 0.78 nm and 0.68 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tian et al. investigated the activity and stability of Al‐ and Ga‐modified YBaCo 4 O 7 catalysts for catalytic soot combustion by isotopic isothermal reactions [125] . The results indicated that the reaction rate of YBa(Co 0.85 Al 0.075 Ga 0.075 ) 4 O 7+δ at 300 °C was ten times higher than CeO 2 ‐based oxides.…”
Section: Rare Earth Oxide‐based Catalysts For Soot Combustionmentioning
confidence: 99%
“…One efficient exhaust gas treatment system is the continuously regenerating particulate trap (CRT) technique, which is based on the use of highly active catalytic materials [3,4]. Over several decades of development, several materials exhibiting high catalytic activity for soot combustion have been identified, including noble metals, transition metal oxides, alkaline metal oxides, perovskite-like oxides and ceria-based oxides [5][6][7][8][9]. However, it remains challenging to fabricate highly active catalytic systems for soot combustion, and developing high-performance catalysts requires an understanding of the properties that affect catalytic activity.…”
mentioning
confidence: 99%